A CAUSAL ADMINISTRATIVE FACTORS MODEL INFLUENCING ORDINARY NATIONAL EDUCATIONAL TEST SCORES OF STUDENTS IN PRIMARY EDUCATIONAL SERVICE AREA OFFICES IN THE EASTERN REGION - เวเบอร์, ปาริชาติ; อนันต์นาวี, ภารดี (Sripatum Review of Humanities and Social Sciences, 2018)
The objectives of this study were to (1) determine the administrative factors that influence the ordinary national educational test scores of students in schools under primary education service area offices in the Eastern region; (2) to develop and validate the concordance of the causal administrative factors model with empirical data; (3) to validate the feasibility of implementing the causal administrative factors model by the experts. The sample, derived by stratified random sampling, consisted of 720 academic teachers in primary schools under the primary education service area offices in the Eastern Region. The employed research instrument was a set of 5-scale rating questionnaire. Basic data were analyzed using descriptive statistics, while LISREL Program was used for verification of construct validity of the model. The feasibility of the model implementation was examined using focus group discussion by experts. The results indicated that the factors influencing ordinary national educational test scores of students in schools under primary education service area offices in the Eastern Region comprised instructional leadership, administrative behavior, teachers’ organizational commitment, being a learning organization of the school, and learner-centered instructional management. The factor having the highest overall influence was the instructional leadership. The factors that had direct influence were instructional leadership and teachers’ organizational commitment. They could be combined to predict students’ ordinary national educational test scores by 43 percent. The factors that had indirect influence were the administrative behavior, being a learning organization of the school, and learner-centered instructional management. The developed model conformed to empirical data at the good level. Also, the experts concluded that the model was appropriate and feasible for implementation.